DİVAN-I HÜMAYUN - Aydın YETKİN (Fırat University, 2019)
In this study, the first place, four thousand years before Christ who has a history dating back to the Turks will be given general information about the structure and functioning of the state. Second, Islam was founded after the Turkish-Islamic States in general, will focus on the structure. Thirdly, the Turks converted to Islam and the Islamization of Turkey after the transition process and the functioning of the state structure, based on the Great Seljuk and Anatolian Seljuk States, will be discussed in general. Finally, the main issue of this study, the highest decision making body of the central organization of the Ottoman Empire, the overall management of the state, legal, political, administrative, financial and military in charge of operations and statements on these areas shall be authorized in the Divan-i Humayun.